High voltage lithium ion battery with wide electrochemical window polymer electrolyte
By using solid polymer electrolytes with PVTF matrix in solid-state lithium-ion batteries and adding LiTFSI and LiDFP, the problem of insufficient compatibility between SPE and high-voltage cathode materials is solved, the expansion of the electrochemical window and the improvement of ionic conductivity are achieved, and the cycle stability and energy density of the battery are significantly improved.
Patent Information
- Application Number
- CN202411036153.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-09-17
- Filing Date
- 2024-07-31
- Publication Date
- 2025-03-18
AI Technical Summary
In existing solid-state lithium-ion batteries, the compatibility between solid polymer electrolyte (SPE) and high-voltage cathode materials is insufficient, resulting in narrow electrochemical windows and unstable oxidation potential, which affects the energy density and cycling performance of the battery.
Poly(vinylidene fluoride-co-trifluoroethylene-co-chlorotrifluoroethylene) (PVTF) is used as the matrix of solid polymer electrolyte, and lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) and lithium difluorophosphate (LiDFP) are added as sacrificial additives to expand the electrochemical window and improve ionic conductivity.
The electrochemical window up to 5.68V and a high ionic conductivity of 1.91×10-3S cm-1 were achieved, which significantly improved the cycle stability and energy density of solid-state lithium-ion batteries, and was able to maintain constant performance of 200 cycles and a high capacity retention rate of 75%.
Smart Images

Figure CN119650830A_ABST
Abstract
Description
Technical Field
[0001] This application claims priority to U.S. patent application No. 18 / 468,736 filed on September 17, 2023, and the disclosure of which is incorporated herein by reference in its entirety. Technical Field
[0002] The present invention generally relates to the field of solid-state lithium-ion battery technology. More specifically, the present invention provides a method for widening the electrochemical window of a polymer electrolyte in a high-voltage lithium-ion battery. Background Art
[0003] Solid-state batteries convert flammable liquid electrolytes into non-flammable solid electrolytes, thereby exhibiting enhanced stability in terms of mechanical and chemical properties, which also significantly extend static and cycle life. Compared with the energy density (250Wh / kg) in traditional lithium batteries (LIBs), the energy density of solid-state batteries is currently close to 400Wh / kg, which provides significant advantages.
[0004] Solid-state lithium-ion batteries (SSLIBs) hold significant promise in meeting the considerable demands of advanced power systems, with the potential to address the energy density, fast charging, and safety prerequisites of upcoming consumer electronics and electric vehicles. The excellent mechanical properties, high heat resistance, and solvent-free / low-solvent characteristics of solid polymer electrolytes (SPEs) ensure their high safety. 1-3 Fabricating SPEs is an effective approach for seeking improved safety and higher energy density in lithium-ion batteries.
[0005] Compared with their solid ceramic electrolyte (SCE) counterparts, SPEs have enhanced large-scale manufacturing processability, which is attributed to their favorable interfacial contact with solid electrodes and good mechanical flexibility. 4-6 Most polymers are compatible with relatively low voltage cathodes. However, only a few SPEs have sufficient oxidation potential to pair effectively with high voltage cathode materials. 0.8 Mn 0.1 Co 0.1 In the presence of aggressive cathodes of O2(NMC811) or 5.0 V LCPO, the carbonyl groups exhibit anodic instability with a thermodynamic tendency to release CO2 and O2. As a result, cells including Li||NMC811 and Li||LCPO exhibit significantly insufficient performance.
[0006] Another challenge comes from the instability of Ni-rich cathodes. The lack of compatibility between SPE and Ni-rich cathodes at higher potentials (potentials above 4.5 V) presents a challenge in the pursuit of further enhancing the performance of SSLIBs. 7-8The energy density challenge of the cathode leads to SPE oxidation, cathode surface reconstruction and transition metal ion dissolution. As a result, this leads to poor cycling performance. 9 .
[0007] The above challenges make it difficult to further enhance the energy density of solid-state lithium-ion batteries. Summary of the invention
[0008] Therefore, the present invention introduces a novel strategy for advancing high-voltage SSLIB in the study of SPE. Specifically, the present invention provides a method to broaden the electrochemical window of SPE.
[0009] In a first aspect, the present invention provides a solid polymer electrolyte based on poly(vinylidene fluoride-co-trifluoroethylene-co-chlorotrifluoroethylene) (PVTF), comprising: a polymer matrix; N,N-dimethylformamide (DMF) solvent; and lithium bis(trifluoromethanesulfonyl)imide (LiTFSI). The solid polymer electrolyte based on PVTF exhibits an excellent electrochemical window of up to 5.68 V, a significantly higher 1.91×10 -3 S cm -1 The ionic conductivity of the PVTF-based solid polymer electrolyte is lower than -38°C. g ).
[0010] According to one embodiment, the polymer matrix includes PVTF with a mass of 0.1 g to 2 g, LiTFSI with a mass of 0.1 g to 2 g, and DMF solvent with a volume of 1 ml to 10 ml.
[0011] According to one embodiment, the PVTF-based solid polymer electrolyte further includes a sacrificial additive.
[0012] According to one embodiment, the sacrificial additive includes lithium difluorophosphate (LiDFP) having a mass of 0.01 g to 0.05 g.
[0013] In a second aspect, the present invention provides a high-voltage solid-state lithium-ion battery with a wide electrochemical window polymer electrolyte, comprising: a cathode material; an anode material; a solid polymer electrolyte. The high-voltage solid-state lithium-ion battery has a constant cycle performance of more than 200 cycles at 0.5C, and an impressively high capacity retention rate of 75%.
[0014] According to one embodiment, the cathode material includes a Ni-rich cathode material or a lithium foil.
[0015] According to one embodiment, the Ni-rich cathode material comprises spinel LiNi 0.5 Mn 1.5 O4(LNMO) particles.
[0016] According to one embodiment, an amorphous conductive cathode-electrolyte interface (CEI) layer is used to encapsulate the LiNi 0.5 Mn 1.5 O4 particles.
[0017] According to one embodiment, the CEI layer includes an inner CEI and an outer CEI, and wherein the inner CEI includes Li3PO4 and LiF.
[0018] According to one embodiment, a cathode material including LNMO particles and a CEI layer exhibits improved rate performance, producing 137 mAh g recorded at 0.1C, 0.2C, 0.5C, 1.0C, and 2C, respectively. -1 , 130mAh g -1 , 125mAh g -1 , 105mAh g -1 and 70mAh g -1 Considerable specific capacity.
[0019] According to one embodiment, the anode material includes lithium foil.
[0020] According to one embodiment, the anode material and the cathode material further include a current collector, one or more active materials, one or more electronically conductive particles, and one or more binders.
[0021] According to one embodiment, the current collector includes aluminum foil or copper foil.
[0022] According to one embodiment, a high voltage solid-state lithium-ion battery can achieve a power of 0.1 mA cm -2 The current density is 0.1 mAh cm -2 It has a stable cycle life of about 2400 hours at a capacity of 1.54 W, showing an extremely low overpotential of 55.7 mV.
[0023] According to one embodiment, when the current density increases to 0.5 mA cm -2 The high-voltage solid-state lithium-ion battery achieves a long cycle life of about 1,600 hours.
[0024] According to the highest occupied molecular orbital (HOMO) energy level, the present invention uses poly(vinylidene fluoride-co-trifluoroethylene-co-chlorotrifluoroethylene) [(PVDF-TrFE-CFE)] (denoted as PVTF) polymer with high oxidation stability as the SPE matrix and for stabilizing LiNi 0.5 Mn 1.5 Sacrificial additive (lithium difluorophosphate, LiDFP) for O4 (LNMO) cathode. Compared with the prior art, the present invention provides the following main advantages: (1) Compared with PSE, PLSE separators exhibit significantly enhanced electrochemical stability, thereby enabling reversible operation of lithium-ion batteries. (2) The design strategy of PLSE is more cost-effective and user-friendly because free-standing PLSE can be obtained via casting and doctor blade coating processes, which simplifies the acquisition of solid electrolytes for lithium-ion batteries compared with the conventional assembly method involving immersing the separator in liquid electrolyte. (3) PLSE exhibits an excellent electrochemical window up to 5.68 V, which exceeds the capability of existing SPE technology. (4) PLSEs have broad utility across various types of lithium-based batteries and exhibit high safety compared to conventional liquid LIBs. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Embodiments of the present invention are described in more detail below with reference to the accompanying drawings, in which:
[0026] Figure 1A Characterizing the redox potentials of cathode materials for lithium-ion batteries and the electrochemical stability windows of conventional solid polymer electrolytes. Figure 1B Schematic illustration showing the serious problems existing in Ni-rich oxide electrode materials. Figure 1C Schematic energy diagram showing polymer electrolytes. g It is the energy interval between the highest occupied molecular orbital (HOMO) and the lowest unoccupied molecular orbital (LUMO) of the polymer electrolyte.
[0027] Figure 2A Shown are schemes representing the HOMO and LUMO levels of PEO, PVTF, PMMA, PAN, and PVDF. Figure 2B Schematic illustration showing the structure of PVTF polymer.
[0028] Figure 3 FTIR patterns of PVTF and PVDF polymers are depicted.
[0029] Figure 4 The strain-stress curves of different SPEs are plotted.
[0030] FIG. 5A to FIG. 5D The EIS patterns at different temperatures ranging from 25 °C to 100 °C are depicted. Figure 5E The corresponding ionic conductivities of the fabricated PSEs are plotted, where the weight ratio of LiTFSI / P(VDF-TrFE-CFE) is varied from 0.1 to 1.5.
[0031] Figure 6 Diagram showing cathode-electrolyte interface (CEI) formation during the charge-discharge process of PLSE.
[0032] Fig. 7A Depicting the linear sweep voltammetry (LSV) measurement results of LNMO|PSE|Li and LNMO|PLSE|Li solid-state batteries. Figure 7B Arrhenius plots of PSE and PLSE are plotted. σ is the ionic conductivity, and T is the temperature. Figure 7C Plotted is the ionic conductivity and electrochemical window of the fabricated SPE (at room temperature) compared to other workpieces.
[0033] Fig. 8A SEM images of the fabricated PLSE are shown. Figure 8B Shown are cross-sectional SEM images of the fabricated PLSE.
[0034] Fig. 9 The DSC curves of the fabricated PSE and PLSE are depicted.
[0035] Fig. 10A Depict the Tafel plots of Li|PSE|Li battery and Li|PLSE|Li battery. Fig. 10B Depicted is the chronoamperometry profile of a Li|PLSE|Li cell at a polarization voltage of 20 mV. Inset is the EIS curves before and after polarization. Fig. 10C Depicted is the chronoamperometry profile of a Li|PSE|Li cell at a polarization voltage of 20 mV. Inset is the EIS curves before and after polarization. Fig. 10D Plotted at 0.1 mA cm -2 Voltage profiles of lithium plating / stripping cycles of Li|PLSE|Li cells at current densities of 2.5 and 1.5 and the corresponding EIS patterns under different charge conditions. Fig.10E Plotted at 0.5 mA cm -2 Voltage profiles of lithium plating / stripping cycles of Li|PLSE|Li cells at current densities of 2.5 and 1.5 and the corresponding EIS patterns under different charge conditions. Fig.10F Depicting the voltage profiles of lithium plating / stripping cycles of Li|PLSE|Li cells at different current densities.
[0036] Fig.11 HRTEM images of a LNMO cathode with PSE after 5 cycles at 0.5C (where the corresponding inset shows the crystal plane of LNMO), and HRTEM images of a LNMO cathode with PLSE after 5 cycles at 0.5C (where the corresponding inset shows the thickness of the CEI layer) are shown.
[0037] Fig.12 Shown are EDX mapping images of the LNMO cathode with PLSE after 5 cycles at 0.5C.
[0038] Fig.13 C2HO on the LNMO surface with PLSE at the end of the 5th cycle - PO2F2 - ,PO2F-,OH - 、NiO - 、NiF - PO3 - 、LiF2 - , 3D ToF-SIMS of F-surface.
[0039] Fig.14A C2HO on the LNMO surface with PLSE at the end of the 5th cycle - TOF-SIMS negative ion mapping of surfaces - depth profile. Fig. 14B PO3 on the LNMO surface with PLSE at the end of the 5th cycle - TOF-SIMS negative ion mapping of surfaces - depth profile. Fig. 14C TOF-SIMS negative ion mapping-depth profile of PO2F-surface on LNMO surface with PLSE at the end of the 5th cycle is shown. Fig.14D Demonstration of PO2F2 on LNMO surface with PLSE at the end of the 5th cycle - TOF-SIMS negative ion mapping of surfaces - depth profile. Fig.14E The OH on the LNMO surface with PLSE at the end of the 5th cycle is shown. - TOF-SIMS negative ion mapping of surfaces - depth profile. Fig.14F The F on the LNMO surface with PLSE at the end of the 5th cycle is shown. - TOF-SIMS negative ion mapping of surfaces - depth profile. Figure 14G NiO on LNMO surface showing PLSE at the end of the 5th cycle - TOF-SIMS negative ion mapping of surfaces - depth profile. Fig.14H NiF on LNMO surface showing PLSE at the end of the 5th cycle - TOF-SIMS negative ion mapping of surfaces - depth profile. Fig.14I Demonstration of LiF2 on LNMO surface with PLSE at the end of the 5th cycle - TOF-SIMS negative ion mapping of surfaces - depth profile.
[0040] Fig.15 Depth profiles of several secondary ion fragmentations at the cycled LNMO surface by sputtering via ToF-SIMS are depicted.
[0041] Fig.16Depicted are the XRD results of LNMO cathode cycled under PSE and PLSE after 5 cycles at 0.5 C in the fresh state.
[0042] Fig.17A Depicted is the XPS survey of the LNMO cathode cycled under PSE and PLSE after 5 cycles at 0.5 C in the fresh state. Fig. 17B Depicted are the Mn2p of the LNMO cathode cycled under PSE and PLSE after five cycles at 0.5 C in the fresh state. Fig. 17C Depicted are the Ni 2p of the LNMO cathode cycled under PSE and PLSE after five cycles at 0.5 C in the fresh state.
[0043] Fig.18 XPS C 1s, F 1s, and P1s spectra of the LNMO cathode surface with PSE and PLSE after 5 cycles at 0.5C are depicted.
[0044] Fig.19 Depicted are XPS survey, C 1s, F 1s, and P 2p of a LNMO cathode cycled under PLSE after 50 cycles at 0.5 C in the fresh state.
[0045] Fig. 20 The chemical composition of the CEI layer obtained by quantitative XPS analysis including XPS survey results and fitted XPS spectra is shown.
[0046] Fig.21 The proposed decomposition mechanism of LiDFP-containing PLSE at a Ni-rich cathode is demonstrated.
[0047] Fig.22A Plotted at 0.5mV s -1 CV curves of LNMO|PLSE|Li battery. Fig. 22B Plotting the rate performance of LNMO|PLSE|Li cells at different rates. Fig. 22C The corresponding GCD curves of the LNMO|PLSE|Li battery are plotted. Fig.22D Plotted the cycling performance and CE of LNMO|PSE|Li and LNMO|PLSE|Li batteries at 0.5C. Fig.22E A comparison of cycle life between the present invention and the prior art is shown.
[0048] Fig.23 Plotted at 0.5mV s -1 CV curve of LNMO|PSE|Li battery.
[0049] Fig.24 Selected GCD curves of LNMO|PLSE|Li cells at 0.5C are plotted. DETAILED DESCRIPTION
[0050] The present invention will be described in detail by the following examples and accompanying drawings. It should be understood that the specific embodiments are provided for illustrative purposes only and should not be interpreted in a limiting manner. It will be appreciated by those skilled in the art that the present invention described herein is susceptible to changes and modifications other than those specifically described.
[0051] The present invention includes all such changes and modifications. The present invention also includes all steps and features referenced or indicated individually or collectively in the specification, and any and all combinations of any two or more of the steps or features. Other aspects and advantages of the present invention will be apparent to those skilled in the art by reading the subsequent description.
[0052] As in Figure 1A As observed in Figure 1A The reported electrolyte stability windows for various polymer electrolytes and potential electrode materials are presented. Conventional solid polymer electrolytes include poly(ethylene oxide) (PEO), polyacrylonitrile (PAN), polyvinylidene fluoride (PVDF), polymerized 1,3-dioxolane (PDOL), poly(vinylidene fluoride-co-hexafluoropropylene) (PVDF-HFP), and poly(vinyl ethylene carbonate) (PVEC). Most polymers are compatible with relatively low voltage cathodes such as LiCoO2 (LCO) or LiFePO4 (LFP). However, only a few SPEs have sufficient oxidation potential to be compatible with cathodes such as LiNi 0.5 Mn 1.5 The high-voltage cathode materials of O4 (LNMO), LiCoMnO4 (LCMO) and LiCoPO4 (LCPO) are effectively paired.
[0053] Steering Figure 1B , which shows a schematic illustration of the serious problems existing in Ni-rich oxide electrode materials, such as interfacial side reactions, transition metal ion dissolution, and intergranular cracks. The degradation of high-voltage batteries originates from the violent reaction between the oxidized polymer electrolyte and the high-voltage cathode, leading to the formation of surface deposits and undesirable phase changes in the cathode. This can trigger the transition metal ion (TM) n+ ) dissolves at the cathode-electrolyte interface, increasing the charge transfer resistance of the cathode and ultimately leading to degradation of electrochemical performance during cycling. These factors hamper the operation of lithium-ion batteries assembled with high-voltage cathodes.
[0054] In order to mitigate the oxidation of polymer electrolytes and prevent the persistent interaction between the electrolyte and the cathode, the intrinsic stability window of polymer electrolytes must be widened. Past research efforts have focused on the design of artificial solid electrolyte interface (SEI) protective layers incorporating LiF, Li3PO4 or Li3PS4 onto the Li metal surface in order to enhance the interfacial compatibility.
[0055] However, there are still technical challenges to overcome, such as the significantly lower ionic conductivity of solid electrolytes compared to liquid electrolytes, which leads to a significant increase in the internal resistance of the battery, resulting in impaired battery cycle performance and rate capability. On the other hand, high cost is also a factor that restricts the commercialization of all-solid-state batteries.
[0056] In view of this, the present invention develops an environmentally friendly and user-friendly strategy to adjust the electrochemical window of SPE. The present invention provides a PVTF-based solid polymer electrolyte, which includes: a polymer matrix; N,N-dimethylformamide (DMF) solvent; and lithium bis(trifluoromethanesulfonyl)imide (LiTFSI). The PVTF-based solid polymer electrolyte exhibits an excellent electrochemical window of up to 5.68 V, a significantly higher 1.91×10 -3 S cm -1 The ionic conductivity of the PVTF-based solid polymer electrolyte is lower than -38°C. g ).
[0057] Three components were introduced into PLSE, including PVTF polymer, lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) and sacrificial additive lithium difluorophosphate (LiDFP) used as electrolyte for solid lithium-ion batteries. By utilizing LiDFP to stabilize the decomposition of LNMO cathode (called PLSE), the electrochemical window of SPE was effectively extended to 5.68V. Among various SPEs, PVTF matrix with the lowest HOMO energy level showed its inherent antioxidant ability, which can be well coupled with LNMO cathode. This achievement has paved the way for the fabrication of high-voltage Li||LNMO cells, which showed remarkable cycling stability. Li||LNMO cells with modified SPEs showed remarkable performance, demonstrated by constant cycling performance for more than 200 cycles measured at 0.5C, and an impressively high capacity retention of 75%.
[0058] In one of the embodiments, the anode material may be lithium foil.
[0059] In one of the embodiments, the cathode material may be a Ni-rich cathode. The key factor for stabilizing the Ni-rich cathode is a polymer matrix with high oxidation resistance.
[0060] In one of the embodiments, the sacrificial additive may be LiDFP. Incorporation of a cathode-electrolyte interlayer containing LiDFP can alleviate interaction issues within polymer electrolytes of non-aqueous lithium-ion batteries. This approach addresses safety issues while also reducing material and production costs.
[0061] LiDFP was originally proposed as an electrolyte additive to improve the rate capability of graphite||NMC batteries 10 , and was found to improve the low temperature performance of graphite||NMC batteries 11 Such behavior is attributed to the reduction of interfacial impedance after incorporation of LiDFP. It has been shown that LiDFP can produce a compact and thin cathode-electrolyte interface (CEI) rich in fluorophosphate. 12 .
[0062] It is necessary to find a polymer matrix with a relatively low HOMO energy level in order to achieve stable operation of Ni-rich oxide cathodes. However, the presence of salts, impurities, and the interaction between the cathode surface and the electrolyte severely affect the redox potential of the polymer, which can lead to deviations from the HOMO energy of up to 4 eV ( Figure 1C ). Therefore, potential side reactions between the electrode and the electrolyte should be prevented by constructing a compact and electronically insulating cathode-electrolyte phase interface on the cathode.
[0063] In one embodiment, the pyrolysis of the salt produces an amorphous conductive CEI layer encapsulating the LNMO particles, thereby enhancing the kinetics of lithium ion and electron transfer.
[0064] In the present invention, constructing a stable CEI layer including LiF and Li3PO4 on the LNMO cathode proves beneficial to enhance the cycling stability. In addition, the high conductivity exhibited by the engineered PLSE significantly enhances the rate performance of the high-voltage LNMO|SPE|Li cell.
[0065] In another example, a stable CEI-enhanced rate performance was established on a LNMO cathode, resulting in 137 mAh g recorded at 0.1C, 0.2C, 0.5C, 1.0C, and 2C, respectively. -1 , 130mAh g -1 , 125mAh g -1 , 105mAh g -1 and 70mAh g -1 Specific capacity.
[0066] In another embodiment, cathode materials including LiFePO4, NCM 523, and NCM 811 having an operating potential below 5 V are all compatible with the electrolyte of the present invention.
[0067] In one of the embodiments, both tensile strength and ductility improved as the temperature decreased from room temperature to about -196°C.
[0068] The following examples illustrate the invention and are not intended to limit the invention.
[0069] Examples
[0070] Example 1 - Materials and Methods
[0071] Material
[0072] N-methyl-2-pyrrolidone (NMP), N,N-dimethylformamide (DMF), poly(vinylidene fluoride-co-trifluoroethylene-co-chlorotrifluoroethylene) (PVDF-TrFE-CFE), polyvinylidene fluoride (PVDF), poly(ethylene oxide) average Mv 400,000PEO, lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), spinel LiNi 0.5 Mn 1.5 O4 (LNMO) and lithium difluorophosphate (LiDFP) were purchased from Aladdin.
[0073] Characterization methods
[0074] Fourier transform infrared spectra (FTIR) were collected based on PerkinElmer Spectrum II. Raman spectra were detected on WITec alpha300 R Raman System. Differential scanning calorimetry (DSC) experiments were performed using a DSC Q2000 (TA Instruments) with a Tzero disk. Thermogravimetric analysis (TGA) was applied to TG / DTA 6300 to obtain the polymer content in the composite material. Field emission scanning electron microscopy (SEM, FEIQuanta 450FEG) was used to study the morphology of the product. Powder X-ray diffraction (PXRD) was performed on Bruker D2 Phaser equipment at ambient temperature using Cu-Kα radiation and a monochromator. The 30keV Bi3 + Primary ion gun and 1keV Cs + ToF-SIMS analysis was performed on a 5-100 instrument (IONTOF GmbH) with a sputtering gun. The raster size of the image was 50×50 μm 2 , and the sputtering area is 200×200μm 2. The microstructure and chemical composition were examined by field emission scanning electron microscopy SEM (S-4700, Hitachi), high-resolution transmission electron microscopy (TEM; JEOL-2001F) and electron energy loss spectroscopy (EELS) analysis. X-ray photoelectron spectroscopy (XPS; ESCALAB 250) was used to analyze the surface composition details, with C1s peak calibration at 284.8 eV. XPS spectra of O1s, P 2p, F 1s, Li 1s and C1s were recorded. The discharged / charged LNMO cathode was gently washed three times with ethylene carbonate (EC) and then dried in a glove box at room temperature for 24 h before measurement.
[0075] Electrochemical measurements
[0076] A Ti||Ti coin cell with the prepared SPE was assembled to measure EIS. The ionic conductivity can be calculated by using the following equation: σ=L / (A*R), Wherein L represents the thickness of the polymer electrolyte, R represents that obtained by the above-mentioned EIS measurement, and S represents the area of the stainless steel.
[0077] EIS measurements were performed on the Li|PLSE|Li symmetric cell with the fabricated PLSE from 10 MHz to 0.01 Hz under 20 mV AC oscillation. + The transfer number of the cation can be calculated according to the following equation: Among them I s and I0 represent the steady-state current and initial current, respectively, R0 and R s Represents the interfacial resistance before and after polarization.
[0078] The electrochemical stability window of the SPE was determined by performing linear sweep voltammetry (LSV) measurements on the assembled Li|SPE|Ti cells. All these electrochemical properties were evaluated using a CHI 760D electrochemical workstation. CR2032 button cells were assembled and electrochemical evaluations were performed using Li foil as anode, LNMO as cathode, and PLSE or PSE as solid polymer electrolyte. All these cycle tests were performed on a Land CT2001A battery test system.
[0079] Computational Calculation
[0080] The electronic structures were calculated by using Gaussian 6.0 software. Hybrid density functional B3LYP with 6-31G* basis set has been used for structure optimization as well as electronic structure calculations.
[0081] Example 2 - Evaluation of polymer matrices for Ni-rich oxide cathodes
[0082] In order to identify the most suitable polymer matrix for the Ni-rich oxide cathode, Gaussian calculations were performed to determine the HOMO energy levels and LUMO energy levels of various polymers. The most widely used descriptors of electrolyte stability are the lowest unoccupied molecular orbital (LUMO) and the highest occupied molecular orbital (HOMO) of the polymer matrix. The lower energy level of the HOMO indicates a higher oxidative stability of the polymer.
[0083] like Figure 2A As shown in Figure 1, PVTF exhibits the lowest energy level of HOMO, indicating that it has the highest oxidative stability among all selected polymers (including PEO, PMMA, PAN and PVDF). In PVTF polymer, stable fluorine atoms surround the carbon chain, thus ensuring the stability of the internal structure of PVTF. ( Figure 2B ).
[0084] refer to Figure 3 Fourier transform infrared spectroscopy (FTIR) was used to analyze the chain conformation of PVTF and PVDF. PVTF showed a mixed sequence of random TGTG (where T represents trans and G represents inter-twist), TTTG, and TTTT sequences. 13 PVTF polymers contain a polar β phase with an all-trans (TTTT) conformation, whereas the β phase is absent in conventional PVDF polymers.
[0085] Steering Figure 4 The mechanical properties of the selected polymers were also compared by stress-strain testing when compared with other conventional polymers. The results showed that PVTF exhibited the highest elongation (150%) and the highest yield strength (4.8 mPa). Based on the high-voltage compatibility and mechanical strength of PVTF, PVTF was selected as the polymer matrix to fabricate SPEs with rich Ni oxide cathodes. The salt concentration of PVTF-based SPEs was optimized and the corresponding SPEs were labeled as PVTF. x (where x represents the weight ratio of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) to PVTF).
[0086] Furthermore, the TTTT conformation confers high polarity to PVTF, allowing it to accommodate significant salt contents up to 150%. FIG. 5A to FIG. 5D The PVTF obtained at different temperatures ranging from 25°C to 100°C is shown in x The electrochemical impedance spectroscopy (EIS) results and Figure 5E The corresponding ionic conductivities are summarized in .
[0087] PVTF 1.5 and PVTF 1.0Both exhibit relatively high ionic conductivities at room temperature, measured at 1.90 mS cm -1 and 1.40 mS cm -1 However, PVTF 1.5 The separator experienced cracking issues during the battery assembly process. Considering the mechanical strength, PVTF was selected 1.0 Serves as a polymer matrix for subsequent modifications.
[0088] Example 3 - Preparation of PSE and PLSE membranes
[0089] For the PSE separator, PVDF-TrFE-CFE polymer (0.5 g) was added to a beaker containing 5 ml of DMF, and then LiTFSI (0.5 g) was dissolved in the DMF solution. Then, the solution was stirred for 2 h and heated at 70 ° C. Finally, the clear solution was dropped onto a glass plate and dried in an oven at 50 ° C for 8 h to remove residual DMF.
[0090] For the PLSE separator, PVDF-TrFE-CFE polymer (0.5 g) was added to a beaker containing 5 ml of DMF, and then LiTFSI (0.5 g) and LiDFP (0.025 g) were dissolved in the DMF solution. Then, the solution was stirred for 2 h and heated at 70 ° C. Finally, the clear solution was dropped onto a glass plate and dried in an oven at 50 ° C for 8 h to remove residual DMF.
[0091] Hu et al. have demonstrated that the formation of a robust phase interface containing LiF and Li3PO4 by the decomposition of LiDFP 14 .like Figure 6 As depicted in Figure 2, the protective phase interface inhibits the dissolution of transition metals and cathode surface reconstruction. This inhibition promotes the uniform distribution of Li within the cathode, effectively relieving strain and preventing crack formation.
[0092] Example 4 - Characterization of PSE and PLSE Membranes
[0093] The electrochemical stability of the developed PVTF-based SPE without LiDFP (PSE) and PLSE was examined on assembled Li||Ti cells. The LiDFP additive was sacrificed in advance to achieve a high voltage up to 5.58 V. 7A to 7C , PLSE shows a significant improvement over PSE at ambient temperature (1.41×10 -3 S cm -1 , 0.135 eV) and significantly higher ionic conductivity (1.91×10 -3 S cm -1) and a lower energy barrier (0.129 Ev). Obviously, PLSE exhibits the widest electrochemical window and the highest ionic conductivity compared with previously reported artifacts. This result is caused by the synergistic effect between LiDFP and PVTF.
[0094] according to Fig. 8A As shown in the SEM images, PLSE exhibits a dense morphology with pores of different sizes, which is beneficial for ion transport. Figure 8B According to the cross-sectional SEM image in Figure 2, the thickness of the PLSE is about 71 μm.
[0095] In addition, as indicated by the differential scanning calorimetry (DSC) results of SPE ( Fig. 9 ), both PLSE and PSE exhibit a glass transition temperature (T) of about -38.8°C. g ). This indicates that the PVTF polymer segments are able to move above -38.8 °C, thus achieving high ionic conductivity at room temperature.
[0096] The ion transfer kinetics at the interface achieved by PSE and PLSE can be elucidated by the exchange current density (i0) measured using a Li|SPE|Li symmetric cell. Fig. 10A , the i0 value (2.14 mA cm - 2) Greater than the i0 value of PSE (0.26mA cm -2 ), indicating fast Li + Transfer kinetics. This feature of PLSE can be extended to Li + Transport kinetics. Li+ Calculated by the method reported in the literature 29 , which is 0.5( Fig. 10B ) and 0.45( Fig. 10C ). The higher t of PLSE Li+ and ionic conductivity ensures the promotion of Li + transport, which not only greatly enhances ion mobility but also promotes Li + Uniform diffusion and deposition.
[0097] Example 5 - Preparation of Li|PSE|Li battery, Li|PLSE|Li battery and LNMO|SPE|Li battery
[0098] Li|PSE|Li cells and Li|PLSE|Li cells were assembled using Li foil as anode and cathode and PLSE or PSE as SPE in CR2032 button cells for electrochemical measurements. LNMO|PSE|Li cells and LNMO|PLSE|Li cells were assembled using Li foil as anode and LNMO as cathode and PLSE or PSE as SPE in CR2032 button cells for electrochemical measurements. All these assembly processes were performed in a glove box.
[0099] LNMO powder was coated on a plate with a surface area of 2 mg cm -2 The Al foil with high mass was used as LNMO cathode (LNMO:PVDF:carbon black=8:1:1).
[0100] like Fig. 10D As shown in the figure, the Li|PLSE|Li symmetric cell has a good performance at 0.1 mA cm -2 The current density is 0.1 mAh cm -2 The PLSE exhibited a stable cycle life of 2400 h at a capacity of 1.3 MW, showing an extremely low overpotential of 55.7 mV. The interfacial resistance appears to decrease from 380 Ω to 85 Ω and remains stable over a 2400 h cycle period. This is a strong demonstration of the intrinsic stability of the Li anode conferred by the fabricated PLSE and excludes the possibility of “soft shorting”. When the current density is increased to 0.5 mA cm -2 A long cycle life of 1600h is also achieved. Fig.10E The Li|PLSE|Li symmetric cell exhibits a low overpotential of 68 mV after 1600 h of cycling, further demonstrating the role of SPE in Li + The corresponding EIS pattern is shown in Fig.10E The right side of the graph shows a downward trend and remains at a stable value of 120Ω during the 1600 h cycle. -2 Up to 1.0 mA cm -2 The Li|PLSE|Li symmetric battery exhibits slightly lower voltage hysteresis ( Fig.10F ), which confirms the high ionic conductivity of PLSE. The high ionic conductivity, good interfacial compatibility between PLSE and electrodes, and enhanced Li + The transfer kinetics contribute to the excellent rate performance and long-cycle stability of Li||Li symmetric cells.
[0101] Furthermore, high-resolution transmission electron microscopy (HRTEM) analysis was performed to characterize the detailed interfacial structural features of the LNMO cathode cycled under PSE and PLSE. Fig.11, no CEI layer was observed in the LNMO cathode cycled under PSE. The inset presents high-resolution lattice fringes with an inter-plane spacing of 0.472 nm, indicating the (111) crystal plane of the LNMO cathode. In contrast, a thin protective layer with an average thickness of 4.5 nm was detected in the LNMO cathode cycled under PLSE, an amorphous phase that facilitates ion transport in subsequent electrochemical reactions. The uniform distribution of O, P, and F elements strongly demonstrates the homogeneity and reliability of the artificial CEI strategy ( Fig.12 ).
[0102] like Fig.13 and FIG. 14A to FIG. 14I As shown, time-of-flight secondary ion mass spectrometry (ToF-SIMS) chemical mapping collected on the LNMO cathode after the fifth cycle revealed a - ) and organic matter (represented by OH - and C2HO - The phase interface products (represented by) appear on the surface of LNMO particles. Fig.15 As shown in Figure 2, the normalized depth profile of ToF-SIMS reveals the complex multilayer nature of CEI on the LNMO surface region. 32 Organic matter (composed of OH - 、CH2 - and C2HO - The intensity of ( ) changes from high to low, indicating that organic substances mainly appear at the outer layer. However, the intensity of the inorganic components composed of LiF and Li3PO4 changes from low to high. This reveals that the CEI on the LNMO surface consists of an inner inorganic layer and an outer organic layer.
[0103] The LNMO|SPE|Li battery delivered excellent capacity, exhibited good rate performance, and maintained a stable cycle life. This strategy for widening the electrochemical window of SPE can be widely used in lithium-based batteries, including lithium-oxygen batteries and lithium-sulfur batteries, which can greatly promote the development of various high-voltage lithium-based batteries.
[0104] Example 6-CEI Components
[0105] To characterize the CEI components, Fig.16 The X-ray diffraction (XRD) pattern of a CEI sample collected from a cell using PLSE is shown in Figure 1. It reveals the coexistence of three crystalline phases: LNMO, LiF, and Li3PO4. Li3PO4 was identified in CEI by other studies and is believed to be a decomposition product of the LiDFP salt. 14,15 .
[0106] Ex situ X-ray photoelectron spectroscopy (XPS) was also performed to analyze the chemical composition of CEI on LNMO after one cycle. The relationship between the structural stability of the CEI film and LNMO can be seen in the XPS investigation of cathodes cycled under PSE and PLSE after 5 cycles at 0.5C in the fresh state ( Fig.17A )、Mn 2p( Fig. 17B ) and Ni 2p( Fig. 17C ) spectra. The valence states of the elements in LNMO did not change significantly, which proves that the structural stability of LNMO can be maintained when assembled with PSE or PLSE. The C1s spectra of cathodes recovered from PLSE and PSE show three pairs of peaks corresponding to Li2CO3, CO and CC / CH, respectively ( Fig.18 ).
[0107] In addition, a higher LiF concentration was detected in the CEI produced by PLSE when compared with that of PSE ( Fig.18 ). Three peaks were observed in the P 2p spectrum of the cathode recovered from PLSE ( Fig.18 ), the three peaks are related to PF organic matter and Li3PO4 generated by the decomposition of LiDFP at the cathode / electrolyte interface 16,17 .
[0108] Li3PO4 has high ionic conductivity and low interfacial barrier, which facilitates fast ion transport at solid-solid interfaces 18-21 By implication, CEI includes organic substances (such as ROLi and ROCO2Li 22 ) and inorganic substances (including LiF, Li3PO4 and Li2CO3 22-24 ). The LiDFP-derived CEI maintained a content similar to that during the initial formation process even after 50 cycles ( Fig.19 ), so this amorphous CEI can provide a durable interface for stable electrochemical reactions.
[0109] Quantitative analysis of the XPS data was performed to make a definitive interpretation. Fig. 20 The surface materials (including CEI components, carbon additives, etc.) on the LNMO electrode and their relative amounts in different states are shown in Figure 1. The main CEI components on the LNMO cathode in a fully charged battery are Li2CO3, Li3PO4, LiF, and organic compounds containing CO and CH bonds. 23The increase in the amount of LiF and Li3PO4 in the CEI on the cathode surface indicates the formation of a robust CEI on the LNMO surface, which is expected to achieve stable operation of the full cell. These XPS results are consistent with the ToF-SIMS and XRD results, indicating that the CEI on LNMO with PLSE is composed of abundant Li3PO4 and LiF. The robust CEI is expected to enhance the cycling stability of LNMO. Fig.21 The CEI formation mechanism of PLSE was proposed in which the decomposition of LiDFP generates positive components (Li3PO4 and LiF) and negative components (HF, an attacker on the LNMO surface) at the SPE / electrode interface.
[0110] However, during the lithiation of the LNMO cathode, Li + will be combined with HF to convert to LiF. Therefore, LiDFP has great potential to stabilize the cycling performance of LNMO. The CEI can be divided into two parts: internal CEI and external CEI. The internal CEI is most likely composed of Li3PO4 and LiF, while the external CEI is most likely composed of organic oligomers produced by the reaction between PLSE and LNMO cathode, thereby enhancing the interfacial compatibility.
[0111] Considering the significance of the stable CEI formed by PLSE, the electrochemical performance of solid Li||LNMO batteries was evaluated by assembling solid Li||LNMO batteries using Li foil and commercial LNMO cathode combined with PLSE. Fig.22A The cyclic voltammetry (CV) curves of LNMO with PLSE are shown, where a pair of intensity peaks at 4.9 / 4.5 V are assigned to Ni 2+ / Ni 4+ The redox couple. The well-overlapped CV curves in the subsequent cycles indicate the considerable stability of the Li||LNMO full cell with PLSE. However, when compared with the Li|PLSE|LNMO full cell, the Li|PSE|LNMO full cell exhibits a higher polarization, revealing a more compatible nature between the PLSE and the LNMO cathode ( Fig.23 ).
[0112] Example 7-Rate performance of solid Li||LNMO batteries based on PLSE and PSE
[0113] like Fig. 22B As shown in Figure 2, the results indicate that as the current density increases step by step, the cells with PLSE exhibit better specific capacity compared to the cells using PSE. The Li||LNMO full cells with PLSE deliver 137 mAh g recorded at 0.1C, 0.2C, 0.5C, 1.0C, and 2C, respectively. -1 , 130mAh g -1 , 125mAh g -1, 105mAh g -1 and 70mAh g -1 Appropriate specific capacity.
[0114] It is worth noting that Fig. 22C The corresponding constant current charge-discharge (GCD) curves of Li||LNMO full cells with PLSE at various current densities are shown in Figure 2, showing a discharge plateau of 4.7 V and a charge plateau of 4.75 V at 0.1 C, and the discharge / charge overpotential becomes larger with increasing rate.
[0115] In addition, the long-term cycling stability of solid Li||LNMO full cells with PLSE or PSE was tested at a current density of 0.5C (e.g. Fig.22D ), where the corresponding selected GCD curve is presented in Fig.24 The solid Li||LNMO full cell with PLSE maintains a stable cycle life of 200 cycles with a high capacity retention (75%), while the solid Li||LNMO full cell with PSE experiences rapid capacity decay during cycling. The initial low Coulombic efficiency observed for the solid Li||LNMO full cell with PLSE is attributed to the formation of CEI induced by the interfacial reaction between PLSE and LNMO. This aspect is highly significant for achieving excellent cycle durability.
[0116] The electrochemical performance of the solid Li||LNMO full cell with the fabricated PLSE is significantly superior to that of most previously reported counterparts using different polymer matrices such as PVDF-HFP, PEO, and PAN or with a cathode regulated by CEI ( Fig.22E ) 25-31 All these results have demonstrated that a well-designed PLSE with CEI regulation can enable solid-state lithium-ion batteries (LIBs) with considerable capacity, impressive rate capability, excellent stability, and extended cycle life, all in a dendrite-free manner.
[0117] In summary, the present invention provides a novel SPE design strategy to effectively widen the electrochemical window of SPE up to 5.68V, which is attributed to the high antioxidant stability and CEI regulation function of the fabricated PLSE. The pyrolysis of LiDFP leads to the formation of CEI. Ex situ XPS, HRTEM and ToF-SIMS results reveal that CEI mainly exists on the surface of LNMO particles. It exhibits a multilayer structure, including an internal CEI composed of durable LiF and Li3PO4 and an external CEI composed of loosely bound organic oligomers. The establishment of a stable CEI on the LNMO cathode achieves excellent cycle stability, thereby maintaining a lifespan of 200 cycles at 0.5C and a high capacity retention rate of 75%. In addition, it exhibits significant rate performance, delivering 137mAh g at 0.1C, 0.2C, 0.5C, 1.0C and 2C rates, respectively. -1 , 130mAh g -1 , 125mAh g -1 , 105mAh g -1 and 70mAh g -1 A considerable specific capacity.
[0118] definition
[0119] Throughout this specification, unless the context requires otherwise, the word "comprise" or variations such as "comprises" or "comprising" will be understood to imply the inclusion of the stated integer or groups of integers, but not the exclusion of any other integer or groups of integers. It should also be noted that in this disclosure and particularly in the claims and / or paragraphs, terms such as "comprises", "comprised", "comprising", etc. may have the meanings ascribed to them in U.S. patent law; for example, they allow for elements not expressly recited, but exclude elements that are found in the prior art or that affect the basic or novel characteristics of the invention.
[0120] Furthermore, throughout the present specification and claims, unless the context requires otherwise, the word "include" or variations such as "includes" or "including", will be understood to imply the inclusion of a stated integer or group of integers but not the exclusion of any other integer or group of integers.
[0121] References in this specification to "one embodiment," "an embodiment," "an exemplary embodiment," etc. indicate that the described embodiment may include a particular feature, structure, or characteristic, but every embodiment may not necessarily include the particular feature, structure, or characteristic. Moreover, such phrases do not necessarily refer to the same embodiment. Furthermore, when a particular feature, structure, or characteristic is described in conjunction with an embodiment, it should be understood that it is within the knowledge of a person skilled in the art to affect this feature, structure, or characteristic in conjunction with other embodiments, whether or not explicitly described.
[0122] Other definitions of selected terms used herein can be found in the detailed description of the present invention and are applicable to the entire text. Unless otherwise defined, all other technical terms used herein have the same meaning as those generally understood by those skilled in the art to which the present invention belongs.
[0123] Those skilled in the art will appreciate that, in light of these teachings, alternative embodiments may be implemented without undue experimentation or without departing from the spirit or scope of the invention as set forth in the appended claims. The present invention shall be limited solely by the appended claims, which include all such embodiments and modifications when viewed in conjunction with the above description and the accompanying drawings.
[0124] Industrial Applicability:
[0125] By integrating the excellent stability of the PVTF polymer matrix and utilizing the pyrolysis of LiDFP, high-performance PLSE has been successfully developed. The PLSE of the present invention exhibits advantageous properties such as an extended operating voltage window, cost-effectiveness, excellent ionic conductivity, and the ability to regulate the formation of the SEI layer. The PLSE can operate stably above 4.75V, which is expected to increase the energy density of SSLIBs and show considerable potential in developing high-safety energy storage devices for applications such as large-scale stationary energy storage devices, portable electronic devices, flexible energy storage devices, and other related fields.
[0126] References: The disclosures of the following references are incorporated by reference [1] X. Miao, H. Wang, R. Sun, C. Wang, Z. Zhang, Z. Li, L. Yin, Energy & Environmental Science, 2020, 13, 3780. [2] F. He, W. Tang, X. Zhang, L. Deng, J. Luo, Advanced Materials, 2021, 33, e2105329. [3] J. Wu, L. Yuan, W. Zhang, Z. Li, X. Xie, Y. Huang, Energy & Environmental Science, 2021, 14, 12. [4] L. Han, L. Wang, Z. Chen, Y. Kan, Y. Hu, H. Zhang, X. He, Advanced Functional Materials, 2023, 10.1002 / adfm.202300892. [5] S. Liu, W. Liu, D. Ba, Y. Zhao, Y. Ye, Y. Li, J. Liu, Advanced Materials, 2023, 35, e2110423. [6] C. Wang, H. Liu, Y. Liang, D. Li, X. Zhao, J. Chen, W. Huang, L. Gao, L. Z. Fan, Advanced Functional Materials, 2022, 33. [7] B. Qiu, F. Xu, J. Qiu, M. Yang, G. Zhang, C. He, P. Zhang, H. Mi, J. Ma, Energy Storage Materials, 2023, 60. [8] Y. Chen, Y. Cui, S. Wang, Y. Xiao, J. Niu, J. Huang, F. Wang, S. Chen, Advanced Materials, 2023, 35, e2300982. [9] X. Tang, X. Xu, M. Bai, M. Zhang, H. Wang, Z. Wang, A. Shao, H. Wang, Y. Ma, Advanced Functional Materials, 2022, 33.
[10] K.-E. Kim, J. Y. Jang, I. Park, M.-H. Woo, M.-H. Jeong, W. C. Shin, M. Ue, N.-S. Choi, Electrochemical Communications, 2015, 61, 121.
[11] B. Yang, H. Zhang, L. Yu, W. Fan, D. Huang, Acta Electrochimica Sinica, 2016, 221, 107.
[12] J. Tan, X. Li, Q. Li, Z. Wang, H. Guo, G. Yan, J. Wang, G. Li, "Ionology" 2022, 28, 3233.
[13] Y.-F. Huang, T. Gu, G. Rui, P. Shi, W. Fu, L. Chen, X. Liu, J. Zeng, B. Kang, Z. Yan, F. J. Stadler, L. Zhu, F. Kang, Y.-B. He, Energy & Environmental Science, 2021, 14, 6021.
[14] S.Tan, Z.Shadike, J.Li,
[15] Z. Wang, F. Qi, L. Yin, Y. Shi, C. Sun, B. An, H. M. Cheung, and F. Li, Advanced Energy Materials, 2020, 10.
[16] S. Li, L. Yang, P. Wang, Z. Li, W. Li, H. Liu, X. Cui, Journal of Power Sources, 2020, 471.
[17] X. Cui, J. Zhang, J. Wang, P. Wang, J. Sun, H. Dong, D. Zhao, C. Li, S. Wen, S. Li, ACS Appl Mater Interfaces, 2021, 13, 59580.
[18] NW Li, YX Yin, CP Yang, YG Guo, Advanced Materials, 2016, 28, 1853.
[19] D. Zhao, S. Song, X. Ye, P. Wang, J. Wang, Y. Wei, C. Li, L. Mao, H. Zhang, S. Li, Applied Surface Science, 2019, 491, 595.
[20] D. S. Hall, J. Self, J. R. Dahn, Journal of Physical Chemistry C, 2015, 119, 22322.
[21] J. Wang, D. Zhao, Y. Cong, N. Zhang, P. Wang, X. Fu, X. Cui, ACS Appl Mater Interfaces, 2021, 13, 16939.
[22] H. J. Guo, H. X. Wang, Y. J. Guo, G. X. Liu, J. Wan, Y. X. Song, X. A. Lang, F. F. Jia, F. Y. Wang, Y. G. Guo, R. Wen, L. J. Wan, Journal of the American Chemical Society, 2020, 142, 20752.
[23] J.-N. Zhang, Q. Li, Y. Wang, J. Zheng, X. Yu, H. Li, Energy Storage Materials, 2018, 14, 1.
[24] L. E. S. Verdier, R. Dedryvère, F. Bonhomme, P. Biensan and D. Gonbeau, Journal of the Electrochemical Society, 2007, 154, A1088.
[25] G. Lu, H. Wei, C. Shen, F. Zhou, M. Zhang, Y. Chen, H. Jin, J. Li, G. Chen, J. Wang, S. Wang, ACS Appl Mater Interfaces, 2022, 14, 45476.
[26] LL Lu, ZX Zhu, T. Ma, T. Tian, HX Ju, XX Wang, JL Peng, HB Yao, SH Yu, Advanced Materials, 2022, 34, e2202688.
[27] S. Wang, X. Li, T. Cheng, Y. Liu, Q. Li, M. Bai, X. Liu, H. Geng, W.-Y. Lai, W. Huang, Journal of Materials Chemistry A, 2022, 10, 8761.
[28] Y. Wang, Y. Lv, Y. Su, L. Chen, H. Li, F. Wu, Nano Energy, 2021, 90.
[29] H. Xu, S. Wang, H. Wilson, F. Zhao, A. Manthiram, Chemistry of Materials, 2017, 29, 7206.
[30] H. Zhao, Y. Ren, X. Bo, L. Si, Z. Wei, W. A. Daoud, Written Materials, 2023, 223.
[31] W. Zhao, M. Bai, S. Li, X. Tang, W. Wu, C. Sun, X. Yin, J. Zhou, S. Yuan, Y. Ma, Advanced Functional Materials, 2019, 29.
Claims
1. A solid polymer electrolyte based on poly(vinylidene fluoride-co-trifluoroethylene-co-chlorotrifluoroethylene) (PVTF), characterized in that: The PVTF-based solid polymer electrolyte comprises: polymer matrix; N,N-dimethylformamide solvent; and Lithium bis(trifluoromethanesulfonyl)imide, The PVTF-based solid polymer electrolyte exhibits an electrochemical window of up to 5.68 V and an ionic conductivity of 1.91×10 -3 S cm -1 , and the PVTF-based solid polymer electrolyte has a glass transition temperature (T g ).
2. The PVTF-based solid polymer electrolyte according to claim 1, wherein the polymer matrix comprises PVTF having a mass of 0.1 to 2 g, the mass of the lithium bis(trifluoromethanesulfonyl)imide is 0.1 to 2 g, and the volume of the DMF solvent is 1 to 10 ml. 3 . The PVTF-based solid polymer electrolyte according to claim 1 , wherein the PVTF-based solid polymer electrolyte further comprises a sacrificial additive.
4. The PVTF-based solid polymer electrolyte according to claim 1, wherein the sacrificial additive comprises lithium difluorophosphate having a mass of 0.01 g to 0.05 g.
5. A high voltage solid-state lithium ion battery with a wide electrochemical window polymer electrolyte, characterized in that: The high voltage solid-state lithium-ion battery comprises: Cathode material; Anode material; The solid polymer electrolyte according to claim 1, The high-voltage solid-state lithium-ion battery has a constant cycling performance of more than 200 cycles at 0.5C and a capacity retention rate of about 75%.
6. The high voltage solid-state lithium ion battery according to claim 5, wherein the cathode material comprises a Ni-rich cathode material or a lithium foil.
7. The high voltage solid-state lithium ion battery according to claim 6, wherein the Ni-rich cathode material comprises spinel LiNi 0.5 Mn 1.5 O4 particles.
8. The high voltage solid-state lithium ion battery according to claim 7, wherein the LiNi 0.5 Mn 1.5 O4 particles. 9 . The high voltage solid-state lithium ion battery according to claim 8 , wherein the CEI layer comprises an inner CEI and an outer CEI, and wherein the inner CEI comprises Li 3 PO 4 and LiF.
10. The high voltage solid-state lithium ion battery according to claim 8, wherein the LiNi 0.5 Mn 1.5 The cathode material of the O4 particles and the CEI layer exhibited improved rate performance, producing 137 mAh g recorded at 0.1C, 0.2C, 0.5C, 1.0C and 2C, respectively. -1 , 130mAh g -1 , 125mAh g -1 , 105mAh g -1 and 70mAh g -1 Specific capacity.
11. The high voltage solid-state lithium ion battery of claim 5, wherein the anode material comprises lithium foil.
12. The high voltage solid-state lithium ion battery of claim 5, wherein the anode material and the cathode material further comprise a current collector, one or more active materials, one or more electronically conductive particles, and one or more binders. 13 . The high voltage solid-state lithium ion battery according to claim 12 , wherein the current collector comprises aluminum foil or copper foil.
14. The high-voltage solid-state lithium-ion battery according to claim 5, wherein the high-voltage solid-state lithium-ion battery has a current density of 0.1 mA cm -2 The current density is 0.1 mAh cm -2 It has a cycle life of about 2400 hours at a capacity of 1.38kWh and exhibits an extremely low overpotential of 55.7mV.
15. The high voltage solid-state lithium ion battery according to claim 5, wherein when the current density increases to 0.5 mA cm -2 When charged, the high-voltage solid-state lithium-ion battery achieves a cycle life of approximately 1,600 hours.
Citation Information
Cited By
Method for establishing LIBS quantitative analysis model based on novel neural network
CN120409537A